Enterprise Parking Space Management System - ฤทธิ์ไธสง, ประไพรศรี; บวรรัตนวงศ์, ศิรินญา; ศิริสุขเจริญพร, พรพงศ์; วรรณยศ, กาญจนา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: (1) develop a data collection and management system for monitoring the use of organizational parking areas, and (2) reduce errors in allocating parking spaces while enhancing the efficiency of parking management. The system was developed using Microsoft Visual Basic, with the program written and designed in the Visual Basic programming language.The target group for system evaluation consisted of two experts and three end-users. The research instruments included the organizational parking management support system, a system performance evaluation form, and a user satisfaction survey. The statistical methods used for data analysis were mean and standard deviation.The research findings indicated that the system performance evaluation by experts was at a high level (x̄ = 4.38), and user satisfaction with the system was also at a high level (x̄ = 4.43). These results reflect that the system performs efficiently, meets its intended objectives, and is suitably applicable for practical use.